Real‐world treatment patterns of metastatic non‐small cell lung cancer patients receiving epidermal growth factor receptor tyrosine kinase inhibitors. (15th June 2022) - Shenolikar, Rahul; Liu, Sizhu; Shah, Anne; Tse, Jenny; Cao, Yao; Near, Aimee
Abstract: Background: Several epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKI) have been approved for first‐line (1L) treatment of EGFR‐mutated metastatic non‐small cell lung cancer (mNSCLC) in the United States (US). Real‐world analyses of 1L treatment patterns with EGFR TKIs, including the third‐generation EGFR TKI osimertinib which was most recently approved in 2018, are still sparse. Methods: This retrospective observational study used data from IQVIA's prescription claims (LRx) and medical claims (Dx) databases. mNSCLC patients newly treated with any EGFR TKI in the 1L setting were identified from January 1, 2015 to April 30, 2020; the first date of EGFR TKI (third‐generation osimertinib, first‐generation [erlotinib, gefitinib], or second‐generation [afatinib, dacomitinib]) was the index date. Treatment patterns were reported in the cohorts stratified by 1L EGFR TKI. Results: A total of 2505 patients were included in the study (982 osimertinib, 1060 first‐generation, and 463 second‐generation EGFR TKI). Beginning in 2018, osimertinib became the most common 1L EGFR TKI (66.7%) and in early 2020, it accounted for 90.6% of 1L EGFR TKIs. Nearly all patients (>97%) were treated with 1L EGFR TKI monotherapy. Patients with 1L osimertinib had longer treatment duration compared to patients with 1L first‐ or second‐generation EGFR TKI (median months: 17.8 vs. 8.7 vs. 10.5, respectively; log‐rank test for comparisons with osimertinib p < 0.0001) over median follow‐up times of 9.8, 20.5, and 19.3 months. 32.5% and 36.3% of the first‐ and second‐generation EGFR TKI cohorts, respectively, had evidence of 2L treatment. Osimertinib monotherapy accounted for the majority of 2L treatments (58.3%/60.7%) and 11.3%/8.9% had 2L chemotherapy or immuno‐oncology therapy following 1L first‐ or second‐generation EGFR TKI. Conclusion: In this real‐world study of a US claims database, 1L treatment duration was longer with osimertinib compared with other EGFR TKIs. Future studies with longer follow‐up are recommended to understand treatment patterns after progression on EGFR TKIs. Abstract : Several epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKI) have been approved for first‐line (1L) treatment of EGFR‐mutated metastatic non‐small cell lung cancer (mNSCLC) in the United States. This study leveraged prescription and medical claims databases to describe real‐world 1L treatment patterns and found that 1L treatment duration was longer with osimertinib compared with other EGFR TKIs.